2020
DOI: 10.1029/2020jd033041
|View full text |Cite
|
Sign up to set email alerts
|

Australian Rainfall Anomalies in 2018–2019 Linked to Indo‐Pacific Driver Indices Using ERA5 Reanalyses

Abstract: The 2019 and 2018–2019 periods had record low All‐Australia rainfall in both observations and the ECMWF's Reanalysis 5, or ERA5, data set over 1979–2019. An analysis of the relationships between interannual variability of rainfall and atmospheric circulation, vertically integrated moisture flux, and temperature anomalies using ERA5 alone is undertaken. Both standard driver indices and those that combine the Pacific and Indian Ocean influences are used. Regression fields for low annual Australian rainfall show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…A combination of extreme values in remote drivers of variability, including extreme positive IOD, central-Pacific El Niño, and sustained negative SAM associated with very strong sudden stratospheric warming, exacerbated already dry and hot conditions in spring 2019 to promote one of Australia's deadliest fire seasons (Watterson, 2020;Lim et al, 2021a;Abram et al, 2021, Marshall et al 2021. Further, projected trends toward positive IOD (Cai et al, 2014;Abram et al, 2020) or toward negative TPI (Timbal and Hendon, 2011) may contribute to higher maximum temperatures in the future, particularly in later spring when the tropics exert greater influence on Australia's dynamical heat mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of extreme values in remote drivers of variability, including extreme positive IOD, central-Pacific El Niño, and sustained negative SAM associated with very strong sudden stratospheric warming, exacerbated already dry and hot conditions in spring 2019 to promote one of Australia's deadliest fire seasons (Watterson, 2020;Lim et al, 2021a;Abram et al, 2021, Marshall et al 2021. Further, projected trends toward positive IOD (Cai et al, 2014;Abram et al, 2020) or toward negative TPI (Timbal and Hendon, 2011) may contribute to higher maximum temperatures in the future, particularly in later spring when the tropics exert greater influence on Australia's dynamical heat mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the tropics, the positive phases of El Niño Southern Oscillation (ENSO) in the tropical Pacific and the Indian Ocean Dipole (IOD) in the tropical Indian Ocean are the strongest drivers of high maximum temperatures in Australia in spring, particularly in the south and east (Power et al, 1998;Jones and Trewin, 2000;Saji et al, 2005;Min et al, 2013;White et al, 2014). Many more studies focus on the ENSO and IOD relationships to drier spring conditions (Nicholls et al, 1989;Meyers et al, 2007;Ummenhofer et al, 2009;Risbey et al, 2009a;Watterson, 2010;Cai et al, 2011;Min et al, 2013;Pepler et al, 2014;McIntosh and Hendon, 2018;Watterson, 2020) and to more extreme spring fire weather (Harris and Lucas 2019;Marshall et al 2021). While ENSO and the IOD co-vary significantly in austral spring (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Smith 2004, Power et al 2006. Watterson (2020) found that the spatial average rainfall over Australia (Fig. 1), All-Australia precipitation (AApr), related particularly well with the PID.…”
Section: Introductionmentioning
confidence: 93%
“…The effects of the atmospheric transport of moisture on rainfall have been studied by Taminiau and Haarsma (2007), Gu and Adler (2019), Marshall (2019), Hauser et al (2020), Holgate et al (2020), Ye et al (2020), and others. Watterson (2020) presented regression relationships with various driver indices, including the 'Pacific-Indian Dipole' (PID), which combines the west Pacific and the east Indian Ocean anomalies, as represented in the European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis 5 (ERA5) data (Hersbach et al 2020). The quantities considered included the vertically integrated (from the surface to top of atmosphere) horizontal moisture transport or 'flux' vector.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [67], Xue et al [68], Li et al [69], and Wang et al [70] verified the feasibility of the ERA5 dataset in analyzing climate change on TP. In addition, Josey et al [71], Watterson [72], Tarek et al [73], and Tang et al [74] also used ERA5 temperature and precipitation datasets for hydrology modeling, climate change, and other studies.…”
Section: Climate Datamentioning
confidence: 99%